Investigating the Role of International Phonetic Alphabet to Enhance Highschool Students’ Pronunciation Skill - Chuzaimah, Chuzaimah; Fadli, Falih; Tamrin, Desy Satriyani (Tamaddun Life, 2021)
International Phonetic Alphabet (IPA) has been used to provide a unique symbol for each distinctive sound in a language. The IPA has been widely utilized by linguists and dictionaries with modifications for easier identification. This study focuses on how IPA supports Indonesian EFL learners with their pronunciation practice particularly in senior high school context. The present study is qualitative literary research. First, the researcher collected the data from the questionnaire, second, the researcher identified them and make it into conclusion. The result of the analysis showed that students gave their positive perspective in using the IPA symbols as they believed it could enhance their oral skills and technique for learning pronunciation. Although IPA symbols were regarded as useful and easier to learn, several students thought positively of using the phonetic symbol in their learning, most of them felt it is difficult, since the phonetic symbols each had distinctive symbols resulting in students confused to remember and comprehend. This study implies that while the learning curve is high, students were quite motivated to learn English pronunciation through IPA.